Answer:
The answer to 17 is -8. 2+ = 10 - 12 = -2*4 = -8.
The answer to 18 is 28. 4^2 = 16, 7 + 1 = 9 + 3 = 12, 16 + 12 = 28.
Step-by-step explanation:
Answer:
31
Step-by-step explanation:
Given
x² + 5x - 3 = 0
with a = 1, b = 5, c= - 3 , then
sum of roots x₁ + x₂ = -
= -
= - 5
product of roots =
=
= - 3
Now
(x₁ + x₂)² = x₁² + 2x₁x₂ + x₂² , that is
(- 5)² = x₁² + 2(- 3) + x₂²
25 = x₁² - 6 + x₂² ( add 6 to both sides ), then
x₁² + x₂² = 31
Answer:
Htjeghsjsvwuwvwhwvshvshsvshsvshs
Answer:
should be 6cm
Step-by-step explanation:
if you are looking at a cube
For part A, you simply add the two functions a(x) and b(x). The resulting function is then (a+b)(x) = 5x +2.
For part B, you multiply the functions a(x) and b(x). Using the FOIL method, we obtain, 6x^2 -24x + 20x - 80. Simplifying, we get, (a*b)(x) = 6x^2 -4x - 80.
For part C, you replace x in the function a(x) with the expression from b(x). This results to: a[b(x)] = 3(2x - 8) +10. Simplifying, a[b(x)] = 6x - 14.